Middling folk : three seas, three centuries, one Scots-Irish family - Matthews, Linda H. (Chicago Review Press, 2010)
Telling the stories of those who quietly conducted the business and built the livelihoods that made their societies prosper or fail, this account shows how one Scots-Irish American family, the Hammills - millers and blacksmiths - lived out their lives against the backdrop of the American Revolution, the Civil War, and westward expansion.